The Effectiveness of Pre-Marriage Education Program toward the Mental Readiness of Adolescent in Mekarwangi Residence - Haniroh Nurfachriyah; Rahmi Alendra Yusiyaka (Universitas Negeri Padang, 2022)
Individual readiness and maturity is a must-have for someone who is going to get married. For this reason, the Ministry of Religion is instructed that every prospective bride and groom who will marry must first follow marriage guidance as a step in realizing a sakinah, mawaddah and rahmah family. This research is a field research with a normative-empirical legal research method. This research was conducted at the Bukit Mekarwangi Housing Estate, Tanah Sareal District, Bogor City. Primary data sources are taken from interviews with parents of adolescents and adolescents themselves. Secondary data sources are collected through legal sources, implementation documents, modules and other supporting data. Furthermore, the data were analyzed descriptively. Based on the results of the research conducted, the researchers concluded that: first, pre-marital marriage guidance in Bukit Mekarwangi Housing was in accordance with the technical instructions for implementing marriage guidance. Implementation of the guidance can be said to be effective seen from the organization of activities and the fulfillment of infrastructure at the research site. In addition, it also has a positive impact on the bride and groom. Second, the effect of implementation on the readiness of the bride and groom: mentally and conceptually related to their marriage increases with the increase in new knowledge they get from the material presented.Keywords: Teenagers, Premarital, Counseling